Household expenditure on health in Miag-ao town proper. - Matias, Michelle Grace B.
The study determined the factors affecting household expenditures on health in Miag-ao town Proper. There were 180 respondents coming from eight (8) barangays in the town proper of Miag-ao who were included in the study., The dependent variable in the study is the expenditure of household on health. This is a continuous variable. The independent variables are divided in two two categories: the continuous and the dichotomous variables. The independent and continuous variables included are monthly cash income and household size. The independent and dichotomous variables are preference for primary health care, presence of chronically ill members, presence of terminally ill members, presence of catastrophically ill members and presence of babies in the house. The equation was estimated using ordinary least squares. The results of the linear regression revealed that monthly cash income and presence of babies in the house are significant at 0.01, while the presence of catastrophically ill members is significant 0.10. The unadjusted R-squared is 0.827515. This implies that 83% of the variations on health expenditure is explained by the model.